Correction: Yi et al. A Software Platform for Quadruped Robots with Advanced Manipulation Capabilities. Sensors 2023, 23, 8247 - Jae-Bong Yi; Shady Nasrat; Min-seong Jo; Seung-Joon Yi (Sensors)
In the original publication [...]